The CDK-activating kinase (CAK) Csk1 is required for normal levels of homologous recombination and resistance to DNA damage in fission yeast. - Hilary B Gerber; Yana Pikman; Robert P Fisher (PLoS ONE, 2008)
BACKGROUND: Cyclin-dependent kinases (CDKs) perform essential roles in cell division and gene expression in all eukaryotes. The requirement for an upstream CDK-activating kinase (CAK) is also universally conserved, but the fission yeast Schizosaccharomyces pombe appears to be unique in having two CAKs with both overlapping and specialized functions that can be dissected genetically. The Mcs6 complex--orthologous to metazoan Cdk7/cyclin H/Mat1--activates the cell-cycle CDK, Cdk1, but its non-redundant essential function appears to be in regulation of gene expression, as part of transcription factor TFIIH. The other CAK is Csk1, an ortholog of budding yeast Cak1, which activates all three essential CDKs in S. pombe--Cdk1, Mcs6 and Cdk9, the catalytic subunit of positive transcription elongation factor b (P-TEFb)--but is not itself essential. METHODOLOGY/PRINCIPAL FINDINGS: Cells lacking csk1(+) are viable but hypersensitive to agents that damage DNA or block replication. Csk1 is required for normal levels of homologous recombination (HR), and interacts genetically with components of the HR pathway. Tests of damage sensitivity in csk1, mcs6 and cdk9 mutants indicate that Csk1 acts pleiotropically, through Cdk9 and at least one other target (but not through Mcs6) to preserve genomic integrity. CONCLUSIONS/SIGNIFICANCE: The two CAKs in fission yeast, which differ with respect to their substrate range and preferences for monomeric CDKs versus CDK/cyclin complexes as substrates, also support different functions of the CDK network in vivo. Csk1 plays a non-redundant role in safeguarding genomic integrity. We propose that specialized activation pathways dependent on different CAKs might insulate CDK functions important in DNA damage responses from those capable of triggering mitosis.